An annotated checklist of the aquatic Adephaga (Coleoptera) of Egypt III. Noteridae, Haliplidae and Gyrinidae - Salah, Mohamed; Cueto, Juan Antonio Régil (Zootaxa, 2015)
Data from previous literature were used to compile a checklist of the Egyptian fauna of families Noteridae, Haliplidae and Gyrinidae. A total of 17 species are cited for Egypt, distributed among 8 genera Neohydrocoptus Satô, 1972, Canthydrus Sharp, 1882 and Synchortus Sharp, 1880 (Noteridae); Haliplus Latreille, 1802 (Haliplidae); Dineutus MacLeay, 1825, Gyrinus Geoffroy, 1762, Orectochilus Dejean, 1833 and Orectogyrus Régimbart, 1884 (Gyrinidae). The checklist provides information for each recorded species on the type localities, type specimens, descriptors, distribution and previous published records. The checklist presented here provides a summary that can serve as the basis for future progress in the knowledge of these coleopteran families in Egypt.